CD4 T Cell Responses in Latent and Chronic Viral Infections - Walton, Senta; Mandaric, Sanja; Oxenius, Annette (Frontiers in Immunology, 2013)
The spectrum of tasks which is fulfilled by CD4 T cells in the setting of viral infections is large, ranging from support of CD8 T cells and humoral immunity to exertion of direct antiviral effector functions. While our knowledge about the differentiation pathways, plasticity and memory of CD4 T cell responses in response to acute infections or immunizations has significantly increased during the past years, much less is still known about CD4 T cell differentiation and their beneficial or pathological functions during persistent viral infections. In this review we summarize current knowledge about the differentiation, direct or indirect antiviral effector functions and the regulation of virus-specific CD4 T cells in the setting of persistent latent or active chronic viral infections with a particular emphasis on herpes virus infections for the former and chronic lymphocytic choriomeningitis virus infection for the latter.